Correction: The Relationship between Endogenous Androgens and Body Fat Distribution in Early and Late Postmenopausal Women. - Yuankui Cao; Shaofen Zhang; Shien Zou; Xian Xia (PLoS ONE, 2013)
[This corrects the article DOI: 10.1371/journal.pone.0058448.].